Whole-transcriptome analysis of differentially expressed genes between ray and disc florets and identification of flowering regulatory genes in Chrysanthemum morifolium - Liu, Hua; Jia, Yin; Chai, Yuhong; Wang, Sen; Chen, Haixia; Zhou, Xiumei; Huang, Conglin; Guo, Shuang; Chen, Dongliang (Frontiers in Plant Science, 2022)
Chrysanthemum morifolium has ornamental and economic values. However, there has been minimal research on the morphology of the chrysanthemum florets and related genes. In this study, we used the leaves as a control to screen for differentially expressed genes (DEGs) between ray and disc florets in chrysanthemum flowers. A total of 8,359 genes were differentially expressed between the ray and disc florets, of which 3,005 were up-regulated and 5,354 were down-regulated in the disc florets. We also identified many CYCLOIDEA (CYC) and MCMl/ AGAMOUS/ DEFICIENS/SERUM RESPONSE FACTOR (MADS) genes differentially expressed between the ray and disc florets, and they may be involved in regulating the differential development of the two types of chrysanthemum florets. Furthermore, we isolated a TM6 homolog in C. morifolium, which belongs to Class B floral homeotic MADS-box transcription factor (TF) family and is specifically expressed in disc florets. This gene is highly similar to other TM6 lineage genes, but a single-base deletion at the 3′ end of the open reading frame caused a frame shift and a structural change at the protein’s C-terminus. The gene, CmTM6-mu, was ectopically expressed in Arabidopsis thaliana. Petal and stamen developmental processes were unaffected in transgenic A. thaliana lines; however, the flowering time was earlier than in the wild-type control. Thus, the C-terminal of paleoAP3 appears to be necessary for the functional performance in regulating the development of petals or stamens and CmTM6-mu may be involved in the regulation of flowering time in chrysanthemum. This study may be useful for future research on the differentiation and development of the two types of chrysanthemum florets.